2021
DOI: 10.1186/s13075-021-02498-8
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy, patient-perceived usability, and acceptance of two symptom checkers (Ada and Rheport) in rheumatology: interim results from a randomized controlled crossover trial

Abstract: Background Timely diagnosis and treatment are essential in the effective management of inflammatory rheumatic diseases (IRDs). Symptom checkers (SCs) promise to accelerate diagnosis, reduce misdiagnoses, and guide patients more effectively through the health care system. Although SCs are increasingly used, there exists little supporting evidence. Objective To assess the diagnostic accuracy, patient-perceived usability, and acceptance of two SCs: (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 19 publications
1
49
0
2
Order By: Relevance
“…A first rheumatology-specific study with 34 patients using symptom checkers showed that only 4 out of 21 patients with inflammatory arthritis were given the first diagnosis of rheumatoid arthritis or psoriatic arthritis [ 31 ]. Importantly, we could recently show that the same DDSS, when used by patients with inflammatory rheumatic diseases, displayed the correct diagnoses among the first and overall disease suggestions in 17% (9/54) and 26% (14/54) of the time [ 32 ]. Surprisingly, we found no correlation between the proportion of symptoms correctly extracted and the DDSS diagnostic accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…A first rheumatology-specific study with 34 patients using symptom checkers showed that only 4 out of 21 patients with inflammatory arthritis were given the first diagnosis of rheumatoid arthritis or psoriatic arthritis [ 31 ]. Importantly, we could recently show that the same DDSS, when used by patients with inflammatory rheumatic diseases, displayed the correct diagnoses among the first and overall disease suggestions in 17% (9/54) and 26% (14/54) of the time [ 32 ]. Surprisingly, we found no correlation between the proportion of symptoms correctly extracted and the DDSS diagnostic accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…The use of mobile devices for health purposes has thus become an increasingly accessible commodity for many, and numerous health-related smartphone applications are now available ( 64 , 65 ). These include symptom checkers ( 66 , 67 ) and referral tools ( 68 ) that could be helpful for the screening of early arthritic manifestations in PsO, as well as applications for the passive and active monitoring of disease activity [e.g., wearable sensors applications for the passive monitoring of key disease features ( 45 , 69 , 70 ), self-reporting tools ( 71 )]. Medication adherence could also be improved via notification reminders on personal smartphones ( 72 74 ).…”
Section: E-health Approaches For the Management Of Psoriatic Arthritismentioning
confidence: 99%
“…Symptom checkers are artificial-intelligence (AI)-based tools designed to help patients determining the possible causes of their symptoms and eventually direct them to medical attention. In recent years, the use of internet- and mobile- based support for self-diagnosing has greatly increased, and an increasing number of patients perceive symptom checkers as useful for diagnosis ( 67 , 91 ). In rheumatology, symptom checkers could help reducing diagnostic delay by ensuring quicker referral of patients who are at higher risk of having or developing a rheumatic condition.…”
Section: E-health Approaches For the Management Of Psoriatic Arthritismentioning
confidence: 99%
“…In Deutschland sind aus Sicht der Rheumatologie vor allen Dingen die Applikation ADA ( www.ada.de ) und RhePORT ( www.rheport.de ) [ 5 ] zu nennen. In einer multizentrischen Studie erreichten beide Systeme eine vergleichbare Diagnosegenauigkeit [ 6 ]. ADA gibt dem Nutzer nach Durchlaufen der Fragen des Algorithmus 4 bis 5 gewichtete mögliche Diagnosen und schlägt vor, diese beim Facharzt abklären zu lassen.…”
Section: Einsatzmöglichkeiten In Der Praxisunclassified
“…rheport.de) [5] zu nennen. In einer multizentrischen Studie erreichten beide Systeme eine vergleichbare Diagnosegenauigkeit [6]. ADA gibt dem Nutzer nach Durchlaufen der Fragen des Algorithmus Auch bereits bekannte Patienten müssen sich regelmäßig an der Anmeldung bzw.…”
Section: Zugang Zum Systemunclassified